Incidence of Chronic Thromboembolic Pulmonary Hypertension After Pulmonary Embolism in the Era of Direct Oral Anticoagulants: From the COMMAND VTE Registry‐2 - Nobutaka Ikeda; Yugo Yamashita; Takeshi Morimoto; Ryuki Chatani; Kazuhisa Kaneda; Yuji Nishimoto; Yohei Kobayashi; Satoshi Ikeda; Kitae Kim; Moriaki Inoko; Toru Takase; Shuhei Tsuji; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a life‐threatening complication post‐acute pulmonary embolism (PE). The assessment of CTEPH incidence and risk factors post‐acute PE in the era of direct oral anticoagulants remains insufficient. Methods and Results The COMMAND VTE Registry‐2 (contemporary management and outcomes in patients with venous thromboembolism registry‐2) is a multicenter registry that recruited consecutive patients with acute symptomatic venous thromboembolism from 31 centers across Japan. The primary outcome was to demonstrate the detection rate of CTEPH after acute PE in routine clinical practice. Out of the 5197 patients with venous thromboembolism included in the COMMAND VTE Registry‐2, 2787 were diagnosed with acute PE. Following a median follow‐up duration of 747 days, 48 cases of CTEPH were detected, and the cumulative diagnosis of CTEPH in routine clinical practice was 2.3% at 3 years. Independent risk factors for the detection of CTEPH by multivariable Cox regression analysis included women (hazard ratio [HR] 2.09 [95% CI, 1.05–4.14]), longer interval from symptom onset to diagnosis of PE (each 1 day, HR 1.04 [95% CI, 1.01–1.07]), hypoxemia at diagnosis (HR 2.52 [95% CI, 1.26–5.04]), right heart load (HR 9.28 [95% CI, 3.19–27.00]), lower D‐dimer value (each 1 μg/mL, HR 0.96 [95% CI, 0.92–0.99]), and unprovoked PE (HR 2.77 [95% CI, 1.22–6.30]). Conclusions In the direct oral anticoagulant era, the cumulative diagnosis of CTEPH after acute PE was 2.3% at 3 years, and several independent risk factors for CTEPH were identified, which could be useful for screening a high‐risk population after acute PE.